Analysis of Registered Dietitian Nutritionists (RDNs) Knowledge, Attitudes, and Beliefs on Transgender Nutrition Care in Michigan - J. Ford; E. Colling; D. Hannah; S. Hand (Journal of the Academy of Nutrition and Dietetics, 2024)

Partitioning the sources of sediment organic carbon in South African seagrass meadows - A Bossert; S von der Heyden; J Colling; A Ndhlovu (African Journal of Marine Science, 2024)

A framework for guiding rapid scientific response to extreme environmental events - Simon Collings; Ingrid van Putten; Jess Melbourne-Thomas; Alistair J. Hobday (Ocean & Coastal Management, 2024)

Response of Cyclopia subternata to drought stress – assessment of leaf composition, proteomics and product quality - G.S. Mabizela; M. van der Rijst; M.M. Slabbert; P. Mathabe; M. Muller; D. de Beer; M. Stander; J. Colling; B. Walczak; E. Joubert; C. Bester (South African Journal of Botany, 2023)

To pool or not to pool? Guidelines for pooling samples for use in surveillance testing of infectious diseases in aquatic animals - Emilie Laurin; Krishna Thakur; Peter G. Mohr; Paul Hick; Mark St. J. Crane; Ian A. Gardner; Nicholas J. G. Moody; Axel Colling; Ingo Ernst (Journal of Fish Diseases, 2019)
Samples from multiple animals may be pooled and tested to reduce costs of surveillance for infectious agents in aquatic animal populations. The primary advantage of pooling is increased population‐level coverage when prevalence is low (

Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes - A. M. Garcia; M. C. L. M. Oliveira; C. Odebrecht; J. L. A. Colling; J. P. Vieira; F. L. Rodrigues; R. F. Bastos (Marine Biology Research, 2019)

Ferric Sulphate Coagulant Obtained by Leaching from Coal Tailings - J. C. C. C. Menezes; A. V. Colling; R. A. S. Silva; Rafael Hoppen Dos Santos; I. A. H. Scheneider (Mine Water and the Environment, 2017)

Induction of anthocyanin in the inner epidermis of red onion leaves by environmental stimuli and transient expression of transcription factors - Elizabeth J. Wiltshire; Colin C. Eady; David A. Collings (Plant Cell Reports, 2017)

A temperature-sensitive allele of a putative mRNA splicing helicase down-regulates many cell wall genes and causes radial swelling in Arabidopsis thaliana - Paul A. Howles; Leigh K. Gebbie; David A. Collings; Arvind Varsani; Ronan C. Broad; Stephen Ohms; Rosemary J. Birch; Ann H. Cork; Tony Arioli; Richard E. Williamson (Plant Molecular Biology, 2016)

The effect of movement kinematics on predicting the timing of observed actions - Lincoln J. Colling; William F. Thompson; John Sutton (Experimental Brain Research, 2014)

EURRECA—Estimating Iron Requirements for Deriving Dietary Reference Values - Linda J. Harvey; Cristiana Berti; Amelie Casgrain; Irene Cetin; Rachel Collings; Mirjana Gurinovic; Maria Hermoso; Lee Hooper; Rachel Hurst; Berthold Koletzko; Joy Ngo; Blanca Roman Viñas; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values - Nicola M. Lowe; Fiona C. Dykes; Anna-Louise Skinner; Sujata Patel; Marisol Warthon-Medina; Tamás Decsi; Katalin Fekete; Olga W. Souverein; Carla Dullemeijer; Adriënne E. Cavelaars; Lluis Serra-Majem; Mariela Nissensohn; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Evidence-Based Methodology for Deriving Micronutrient Recommendations - Rosalie A. M. Dhonukshe-Rutten; Jildau Bouwman; Kerry A. Brown; Adriënne E. J. M. Cavelaars; Rachel Collings; Evangelia Grammatikaki; Lisette CPGM de Groot; Mirjana Gurinovic; Linda J. Harvey; Maria Hermoso; Rachel Hurst; Bas Kremer; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Estimating Selenium Requirements for Deriving Dietary Reference Values - Rachel Hurst; Rachel Collings; Linda J. Harvey; Maria King; Lee Hooper; Jildau Bouwman; Mirjana Gurinovic; Susan J. Fairweather-Tait (Critical Reviews in Food Science and Nutrition, 2013)

Response of freshwater microcosm communities to nutrients, fish, and elevated temperature during winter and summer - D. McKee; D. Atkinson; S. E. Collings; J. W. Eaton; A. B. Gill; I. Harvey; K. Hatton; T. Heyes; D. Wilson; B. Moss (Limnology and Oceanography, 2003)
Under conditions of stress, shallow freshwater ecosystems can undergo a state change characterized by the rapid loss of macrophytes and subsequent dominance of phytoplankton. Elevated water temperature may promote such change. Here we report the impact of two warming regimes (continuous 3°C above ambient and 3°C above ambient during summer only), with two nutrient loadings and the presence or absence of fish, on 48 microcosm ecosystems created to mimic shallow pond environments. We found that warming did not significantly encourage phytoplankton blooms, even in combination with increased nutrients and fish. Instead, macrophyte communities remained dominant. Macrophyte‐associated invertebrates (gastropods and ostracods) increased in numbers in the warmed microcosms, potentially helping to stabilize the macrophyte communities. Nevertheless, warming produced trends in water chemistry that could be problematic. It increased phosphorus concentrations, total alkalinity, and conductivity. It decreased pH and oxygen saturation and increased the frequency of severe deoxygenation. These trends were largely independent of the other experimental treatments and support the suggestion that moderate warming has the potential to exacerbate existing eutrophication problems.

Interaction between nickel and iron in the rat - Forrest H. Nielsen; Terrence R. Shuler; Thomas J. Zimmerman; Michael E. Collings; Eric O. Uthus (Biological Trace Element Research, 1979)